Interrelation between dividend policy and corporate reputation in Russian companies - Vavilina A.V. (Ural State University of Economics, 2019)
The paper analyses the formation and development of dividend payment procedures in Russian companies and explores the content of corporate reputation and its components. According to the dividend signaling hypothesis, dividends, being an indicator of profitability and financial stability, act as determinants of a company’s sustainable development. This affects its stock price and forges corporate reputation for investors. The authors examine the dynamics of dividends paid out by the leading Russian companies highlighting the phases of emergence and formation of dividend policy in Russia, industry-specific nature and the dominant type of dividend policy. The authors apply the classification of the types of dividend policy (conservative, moderate and aggressive) and use the methods of analysis and synthesis, econometric modeling (regression model building). The source data include the ratings and statistical evidence provided by the Russian Institute of Directors (RID) as well as statistical data retrieved from online resources. The authors conclude that, since 2001, Russian companies have been paying dividends to win investment attractiveness in the eyes of foreign investors. We suppose, therefore, that the emerging dividend policy is becoming one of the indicators of corporate reputation of Russian companies. The analysis shows no statistically significant dependence of stock prices of Russian companies on the size of dividends paid out, but there is some evidence that dividend signaling hypothesis is being implemented in the Russian economy. The study reveals that aggressive dividend policy prevailing in companies partly owned by the state is due to the specificity of rules and regulations in Russia and ambitions of other companies to improve their reputation among investors.